Coordination and Symmetry Patterns During the Drop Vertical Jump in People With Chronic Ankle Instability and Lateral Ankle Sprain Copers. Issue 8 (1st August 2016) - Doherty, Cailbhe; Bleakley, Chris; Hertel, Jay; Caulfield, Brian; Ryan, John; Sweeney, Kevin; Patterson, Matthew R.; Delahunt, Eamonn
Abstract: Background: The drop vertical jump (DVJ) task has previously been used to identify movement patterns associated with a number of injury types. However, no current research exists evaluating people with chronic ankle instability (CAI) compared with people coping with lateral ankle sprain (LAS) (referred to as "LAS copers") during this task. Objective: The aim of this study was to identify the coping movement and motor control patterns of LAS copers in comparison with individuals with CAI during the DVJ task. Design: This was a case-control study. Methods: Seventy individuals were recruited at convenience within 2-weeks of sustaining a first-time acute LAS injury. One year following recruitment, these individuals were stratified into 2 groups: 28 with CAI and 42 LAS copers. They attended the testing laboratory to complete a DVJ task. Three-dimensional kinematic and sagittal-plane kinetic profiles were plotted for the lower extremity joints of both limbs for the drop jump phase (phase 1) and drop landing phase (phase 2) of the DVJ. The rate of impact modulation relative to body weight during both phases of the DVJ also was determined. Results: Compared with LAS copers, participants with CAI displayed significant increases in hip flexion on their "involved" limb during phase 1 of the DVJ (23° vs 18°) and bilaterally during phase 2 (15° vs 10°). These movement patterns coincided with altered moment-of-force patterns at the hip on the "uninvolved" limb. Limitations: It is unknown whether these movement and motor control patterns preceded or occurred as a result of the initial LAS injury. Conclusions: Participants with CAI displayed hip-centered changes in movement and motor control patterns during a DVJ task compared with LAS copers. The findings of this study may give an indication of the coping mechanism underlying outcome following initial LAS injury.